1997
DOI: 10.1128/jcm.35.8.2174-2177.1997
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric bacteremia due to Staphylococcus warneri: microbiological, epidemiological, and clinical features

Abstract: Between 1991 and 1995, an apparent high rate of Staphylococcus warneri bacteremias at the Royal Children's Hospital, Melbourne, Victoria, Australia, raised the possibility of a virulent nosocomial strain. In a retrospective review of 30 S. warneri bacteremias in children, organisms were viable and verified in 22 episodes, 12 representing significant bacteremias. Of these 12 episodes, 2 pairs shared chromosomal DNA pulsed-field gel electrophoresis patterns in unconnected patients, dispelling concerns about a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…The observation of a PFGE type with several representatives demonstrates the circulation of a single clone in the hospital and community. Previous studies have shown a higher diversity of S. warneri [ 40 ] and the dissemination of a single clone among health professionals [ 41 ]. The paucity of molecular epidemiology studies involving S. warneri hinders understanding the clonality of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of a PFGE type with several representatives demonstrates the circulation of a single clone in the hospital and community. Previous studies have shown a higher diversity of S. warneri [ 40 ] and the dissemination of a single clone among health professionals [ 41 ]. The paucity of molecular epidemiology studies involving S. warneri hinders understanding the clonality of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the coagulase-negative staphylococci (CNS) have been studied extensively because of their pathogenicity and involvement in some kinds of human and animal diseases (5,20,21,23). Furthermore, the strains of several CNS species (i.e., Staphylococcus epidermidis, S. haemolyticus, S. warneri, S. hominis, and S. saprophyticus) were found to have high levels of resistance to various antibiotics (25,30).…”
mentioning
confidence: 99%
“…Although S. warneri represents only 1% of the skin staphylococci in normal individuals [5], it may be associated with various human infections such as septicemia, endocarditis, meningitis, conjunctivitis, and wound infections [5]- [8]. According to previous reports, S. warneri infections were most frequently associated with indwelling devices in patients with underlying immunosuppressive illnesses [7] [8]. All postoperative patients in ICU are in high-risk conditions with indwelling catheters after severely invasive treatments.…”
Section: Resultsmentioning
confidence: 99%